Cytogenetic Analysis of Histone Gene and DNA Methylation in Amazonian Turtles (Chelonia: Podocnemididae) - Costa-Richene, Ana Beatriz P.; Almeida, Bruno R. R.; Tavares, Flávia S.; Frade, Luan F. S.; Sá, André L. A.; Nascimento, Luís A. S.; Nagamachi, Cleusa Y.; Pieczarka, Julio C.; Sampaio, Maria I. C.; Filho, Geraldo N. R; Cardoso, Adauto Lima [UNESP]; Martins, Cesar [UNESP]; et al. (American Chemical Society (ACS), 2025)
Histone genes contain sequences responsible for coding five types of proteins (H1, H2A, H2B, H3, and H4) that are of great importance for chromatin organization. Their transcriptional regulation through DNA methylation has been little studied. Testudines are ancient reptiles with high cytogenetic diversity (2n = 26-68), with a large number of histone gene loci in their karyotype. The aim of this study was to analyze the physical location of the histone genes H2A, H2B, and H4 and the regions rich in 5-methylcytosine (5mC) and 5-hydroxy-methylcytosine (5hmC) in the karyotypes of Podocnemis expansa and Podocnemis unifilis. The results showed that P. expansa and P. unifilis have a diploid number of 2n = 28, NF = 50 and 46, respectively. Fluorescence in situ hybridization (FISH) showed clusters of histone genes in both species, with histone H2A, H2B, and H4 sequences located in the pericentromeric region of several pairs of karyotypes. Interstitial clusters of histone H2A and histone H4 genes were observed in the chromosome arms of P. expansa and P. unifilis. Immunolocalization of 5mC in P. unifilis and P. expansa showed that highly methylated regions are distributed mainly in the centromeres, coinciding with many loci H2A, H2B, and H4 genes, as well as markings observed along chromosome arms and distal regions. In relation to 5hmc, it was observed that most of this epigenetic mark has a dispersed distribution along the chromatids and in the distal regions in P. unifilis and P. expansa. Our findings suggest that ectopic recombination and inversion-type rearrangements may contribute to the dispersion of histone genes in Podocnemis and that DNA hypermethylation may be an important mechanism for the inactivation of these multigens during the cell cycle in the turtles studied.